Ocular Injuries in Earthquake Victims - Muhammad Saeed, Muhammad Saeed; Fuad Ahmad Khan Niazi, Fuad Ahmad Khan Niazi (Journal of Rawalpindi Medical College, 2007)
Background: To determine pattern of ocular injuries sustained during earthquake that hit north of Pakistan in Oct. 2005. Methods: It was a case-control study which included, all thirty-one patients who presented to or were referred to the eye departments of Rawalpindi General Hospital and Holy Family Hospital (both tertiary care teaching hospitals attached to Rawalpindi Medical College). The injuries and their management were documented and analyzed. Results: Ocular injuries were 0.19% of the total patients received at these hospitals. Females were twice more affected than males. Children and young adults were more affected. Most of the patients were residents of Muzaffarabad. Most common presenting complaint was esotropia resulting from cranial nerve palsies followed by lacerations of periorbital skin, fractures of orbital and facial bones and the base of skull and ocular penetrating injuries. Associated injuries were cranial nerve palsies, fractures orbit, facial bones and base of skull. Head injury was common among one third of them. Most common diagnosis was multiple cranial nerve injuries followed by isolated 6th nerve palsy. Conclusion: Pattern of ocular injuries sustained during earthquake is quite different from injuries incurred from other sources of trauma.